Adjusting intervention strategies for mental health of COVID-19 patients: A network analysis based on a survey in Omicron-infected patients - Li, Kuiliang; Luo, Keyong; Zhan, Xiaoqing; Liu, Chang; Li, Ling; Luo, Xi; Ren, Lei; Wang, Lingzhi; Feng, Zhengzhi (Frontiers in Public Health, 2022)
Background: The COVID-19 pandemic had a major impact on people’s mental health. As the SAS-Cov-2 evolves to become less virulent, the number of asymptomatic patients increases. It remains unclear if the mild symptoms are associated with mild perceived stress and mental illness, and the interventions to improve the mental health of the patients are rarely reported. Methods: This cross-sectional study investigated the level of depression, anxiety and perceived stress of 1305 COVID-19 patients who received treatment in the Fangcang shelter hospitals in Shanghai, China. Network analysis was used to explore the relationship among depression, anxiety and perceived stress. Results: The prevalence of depression, anxiety and perceived stress in the patients with Omicron infection were 9.03%, 4.60% and 17.03%, respectively, lower than the prevalence reported during the initial outbreak of COVID-19. "Restlessness (A5)", "Uncontrollable worry (A2)", "Trouble relaxing (A4)" and "Fatigue (D4) " had the highest expected influence values. "Irritability (A6)" and "Uncontrollable (S1)" were bridge symptoms in the network. Comparative analysis of the network identified differences in the network structures between symptomatic and asymptomatic patients. Conclusions: This study investigated the prevalence of depression, anxiety and perceived stress and the correlation among them in Omicron-infected patients in Fangcang shelter hospital, in Shanghai, China. The core symptoms identified in the study provide insight into targeted clinical prevention and intervention of mental health in non-severe Omicron-infected patients.